Molecular docking and pharmacology study to explore bio-active compounds and underlying mechanisms of Caesalpinia bonducella on polycystic ovarian syndrome. (2022) - Hossain, Md Arju; Sharfaraz, Ashik; Hasan, Md Imran; Somadder, Pratul Dipta; Haque, Md Akramul; Sarker, Md Rifat; Alam, Md Monjurul; Wasaf Hasan, Ali Mohamod; Sohel, Md; Rahman, Md Habibur
Abstract: Polycystic ovarian syndrome (PCOS) was effectively treated with Caesalpinia bonducella (CB) although its active components and molecular mechanisms remain undetermined. Through network pharmacology and molecular docking technology, the ultimate goal of this study was to investigate the active ingredients and functions of CB against PCOS. A literature review and PhytochemDB database were used to identify the compounds in CB which were then subjected to an ADMET (Absorption, Distribution, Metabolism, Elimination and Toxicity) assessment. Then, the identified common genes were used for network construction through Enrichr and STRING database and docking were performed in AutoDock software. During ADMET screening, only 19 compounds showed excellent potential biological activity out of 51 active ingredients of CB. Furthermore, we have identified 137 and 1976 genes for target compounds and PCOS, respectively by using several public databases. The findings of gene-compounds network analysis revealed that the active ingredients and target genes of CB against PCOS comprised of 5 phytochemicals and 42 overlapping genes, among these flavone and IL-6 being the top active ingredient and hub proteins, respectively. From the pathway enrichment analysis, cytokine-mediated, IL-17, and TLR signaling pathways were the most significant. PPI and molecular docking analysis indicated that CAT -9.3 kcal/mol, TNF (−8.4 kcal/mol) and IL-6 (−8.3 kcal/mol) proteins were the potential biomarkers of PCOS pathogenesis compared to control drug (clomifene citrate). Applying network pharmacology and molecular docking, the active components and molecular mechanisms of CB against PCOS were initially studied. Our study provides scientific evidence that may support the therapeutic impacts of CB and need to be further validation of active compounds in treatment of PCOS.